I2-Promoted site-selective C–C bond cleavage of aryl methyl ketones as C1 synthons for constructing 5-acyl-1H-pyrazolo[3, 4-b]pyridines. Issue 16 (8th July 2022) - Zhou, You; Wang, Li-Sheng; Lei, Shuang-Gui; Gao, Yun-Xiang; Ma, Jin-Tian; Yu, Zhi-Cheng; Wu, Yan-Dong; Wu, An-Xin
Abstract : A novel iodine promoted [1 + 3 + 2] cleavage cyclization reaction for the synthesis of 1 H -pyrazolo[3, 4- b ]pyridines from aryl methyl ketones, 5-aminopyrazoles and enaminones has been established. Abstract : A novel iodine promoted [1 + 3 + 2] cleavage cyclization reaction for the synthesis of 1 H -pyrazolo[3, 4- b ]pyridines from aryl methyl ketones, 5-aminopyrazoles and enaminones has been established. This transition metal-free catalysis method has simple reaction conditions and good substrate compatibility, and has been demonstrated in the transformation of alkyl and natural molecule-derived enaminones. Mechanistic studies showed that two cyclization pathways affording different key intermediates were involved, but affording the same target product after site-selective cleavage of the unstrained C–C bond of the acyl group.